An early Ottoman history (Liverpool)
xiii, 253 sayfa
Keywords: “The manuscript translated here contains one of the most important texts for understanding the development of early Ottoman historiography in the fifteenth century. The so-called Oxford Anonymous chronicle is a comprehensive history of the Ottoman dynasty in Turkish, compiled from various sources to tell the story of the dynasty from its rise to the year 1484 (AH 889). Like several other histories produced around the same time, some of which it influenced, it presents the Ottomans in the context of wider Islamic history and contains a coherent argument for their superiority over other dynasties. The manuscript had previously belonged to the Dutch orientalist Jacob Golius (d. 1667). Although its history is largely unknown, it was probably a presentation copy made for Sultan Bayezid II (r. 1481-1512). The work itself is a product of Bayezid's patronage, and shows a strong preoccupation with the perennial Ottoman problem of dynastic succession. Fully one third of the manuscript contains an older text recounting in epic terms the struggles of Mehmed I against his brothers (1402-13). The obvious explanation is that when Oxford Anonymous was compiled, Bayezid II was also facing a rival claimant to the throne, his brother Cem Sultan (d. 1495).“ --